Alteração do índice biespectral antes e após estimulação elétrica ou mecânica em cães anestesiados pelo isofluorano - Yamashiro, Laise Michi [UNESP]; Floriano, Beatriz Perez [UNESP]; Pinho, Renata Haddad [UNESP]; Wagatsuma, Juliana Tessalia [UNESP]; Ferreira, Joana Zafalon [UNESP]; Oliva, Valéria Nobre Leal de Souza [UNESP] (Universidade Federal de Santa Maria, 2015)
One of the current methods to assess hypnosis and central depression during anesthesia is the bispectral index (BIS), which generates a number from 0 to 100. The purpose of the present study was to evaluate the changes in BIS during electrical or mechanical supra-maximal stimulation in order to investigate whether there is a relation between this index and motor response to nociception. Seven beagle dogs were included, two males and five females, which were anesthetized with isoflurane at 2.0, 1.8, 1.6, 1.4 and 1.2%. Different types of stimuli were employed at different procedures in the same animals with at least 15 days of interval. The BIS values were recorded during 60 seconds each time and mean values were obtained before (AE) and after (DE) the stimulus. Results were compared through paired t test or Wilcoxon's paired test (P<0.05). Significant differences were found between AE and DE values in almost every isoflurane concentration, as well as between the subtraction of these values, when compared between types of stimuli at 1.8 and 2.0%. In conclusion, the response to supra-maximal stimulation does change BIS values in dogs by decreasing the depth of anesthesia. The use of mechanical stimulation is suggested in order to avoid possible interferences of the electrical current and loss of data reliability.

Uma das formas atuais para se avaliar o grau de hipnose e depressão do sistema nervoso central durante a anestesia é o índice biespectral (BIS), que fornece um valor de 0 a 100. Objetivou-se avaliar as alterações do BIS de cães durante a estimulação elétrica e mecânica supra-máxima e sob diferentes concentrações de isofluorano, a fim de verificar se existe uma relação entre este índice e a resposta motora frente à nocicepção. Utilizaram-se sete cães da raça Beagle, dois machos e cinco fêmeas, anestesiados com isofluorano nas concentrações de 2,0; 1,8; 1,6; 1,4 e 1,2%. Os diferentes tipos de estímulo foram utilizados em procedimentos anestésicos diferentes nos mesmos animais, com intervalo mínimo de 15 dias. Os valores de BIS foram anotados por 60 segundos em cada avaliação, derivando médias antes (AE) e depois (DE) de cada estímulo. Os resultados foram analisados por meio de teste t pareado ou Wilcoxon pareado (P<0,05). Houve diferença significativa entre os valores AE e DE em todas as concentrações de isofluorano, exceto 2,0% no estímulo mecânico. Também foi significativa entre a subtração desses valores, quando comparados entre estímulos, em 1,8 e 2,0%. Conclui-se que a resposta frente a estímulos supra-máximos modifica os valores de BIS em cães por meio da superficialização do plano anestésico. Sugere-se o emprego do modelo mecânico para evitar possíveis interferências de corrente elétrica e perda da confiabilidade dos dados.
Bispectral index changes before and after electrical or mechanical stimulation in isoflurane-anesthetized dogs
Keywords: Inhalation anesthesia; Anesthetic hypnosis; Nociception; dogs; Anestesia por inalação; Hipnose anestésica; Nocicepção; Cães